Aftershock - Jardine, Quintin, 1945- (A Bob Skinner mystery, 2008)
It's the second week of July Trades Holiday in Edinburgh when Deputy Chief Constable Bob Skinner and his men get a call informing them that the body of a young woman has been found on a golf course. It's been there for ten days so she's not a pretty sight. But the way she has been laid out is uncannily familiar. The body has been 'composed', just like the bodies of three other young women in a previous case. Could it be the work of a copycat killer? The murder victim is an art teacher who was having a relationship with the son of a Tory MP. Her ex-boyfriend is a policeman with a reputation as a serious womaniser. It seems the murder trail is getting much too close for comfort...